KAJIAN KESESUAIAN KONDISI PARAMETER OSEANOGRAFI PADA KAWASAN BUDIDAYA RUMPUT LAUT DI KECAMATAN ROTE BARAT LAUT KABUPATEN ROTE NDAO - Alexander S. Tanody (Partner, 2020)
The development of seaweed farming needs to be preceded by a feasibility study to anticipate the failures. Feasibility of oceanographic parameters determine the quality of seaweed farming areas, consist of physical parameters including depth, brightness and current velocity, and chemical environment which is salinity, pH and nitrate concentration in the waters. The study aims to determine the suitability of oceanographic parameters of the seaweed farming areas in the coastal waters of Northwest Rote District. The results showed that the sea surface temperature ranges between 29.77°C - 30.17°C, salinity between 30.67‰ - 31.67 ‰, ranges of current velocity between 0.13 m/s - 0.20 m/s, depth ranges between 3,0 m - 3.69 m, pH ranges between 7.27 - 7.37 and the types of substrate is generally sandy. The suitability analysis showed that the coastal waters in District of Nortwest Rote were classified as quite suitable for seaweed farming. Key Words:  Oceanographic parameters, Seaweed farming, Northwest Rote